A block staining method using ethanolic phosphotungstic acid for the visualisation of collagens in transmission electron microscopy - Astrid Obermayer; Stefan Hainzl; Ulrich Koller; David Lang; Bernd Lamprecht; Walter Stoiber (PLoS ONE, 2026)
Conventional transmission electron microscopic imaging of biological samples requires contrast enhancement by staining with heavy metal salts. The most widely used stains are uranyl acetate and its non-radioactive lanthanoid replacements, and lead citrate. However, these substances proved of limited use for the visualisation of small fibrillar collagens. We therefore developed a preparation of ethanolic phosphotungstic acid (E-PTA) as an improvement to overcome this deficiency. We were able to establish a highly effective and time saving block staining procedure that can be integrated in the dehydration steps. The method reliably visualizes fibrillar collagens, prominently including the small collagen VII anchoring fibrils of the human skin, and various other extracellular matrix components. E-PTA-stained collagen I/III fibrils are conspicuous in transverse and longitudinal section, accurately showing the characteristic banding pattern in the latter. The new E-PTA based block staining method also clearly depicts all relevant intracellular structures, particularly accentuating keratin fibres and desmosomal and hemidesmosomal plaques. We therefore conclude that beyond the visualization of collagen, this method is also a fast, inexpensive and versatile non-radioactive alternative to standard staining methods.